Answer:
(x - 2)^2 + (y + 1)^2 = 26
Explanation:
A circle with center O(2, -1) that passes through the point A(3, 4).
=> The radius of this circle is OA which could be calculated by:
OA = sqrt[(3 - 2)^2 + (4 - (-1))^2] = sqrt[1^2 + 5^2] = sqrt[26]
The equation of a circle with center O(a, b) and radius r could be written as:
(x - a)^2 + (y - b)^2 = r^2
=> The equation of circle O above with center O(2, -1) and radius = sqrt(26) is shown as:
(x - 2)^2 + (y - (-1))^2 = (sqrt(26))^2
<=>(x - 2)^2 + (y + 1)^2 = 26
Hope this helps!